Hugo Grotius újraolvasva, avagy a „Nemzetközi jog atyja” gondolatai a XXI. század elejének nemzetközi jogában - Szemesi, Sándor (Debreceni Jogi Műhely, 2004)
There are several theories when the birth date of international law was. Hugo Grotius (1583-1645) was the first who systematized these specific rules and raised it to a scientific level. In this essay I examine how Grotius thought about important institutions of international law and what kind of impact these considerations have to our modern age.War cannot be seen only as an unlawful act, because most of the original human instincts can be recognized in fighting to each other. This point of view proclaims that international law does not denounce war generally. Existence of international law is important to determine the rules of warfare. To suit to the criterions of lawful war, a war should perform two requirements: opposite parties have to be main authorities in their state and both of them have to keep special formal rules during their fight. Main supremacy means that this power is absolute in its territory, so there are no other relevant human factors to limit it. In our age we have to mention that this criterion is no longer applicable without reservation, because the attack against USA on 11th September 2001 demonstrated that not only states can fight to each other.Grotius gives importance to the reasons of war too. Three reasons exist: defence, regain possession and punishment. Defence means self-defence, which is a right for everybody to protect himself against unlawful injuries, but this solution has to be the last one. Self-defence can be applicable only if it is necessary, sudden and proportional. After the attack against USA a question was born: is it possible to protect before the real attack, when the enemy is in the period of planning an injury. This preventive self-defence is supported by USA, but UN appreciates the right to self-defence only if there is an armed attack against the state. According to Grotius reasons of war can be pretexts or real reasons. Fear of uncertainty can be a pretext for example, because it is not the most proportional instrument to avoid conflict.Grotius examines not only ius ad bellum but ius in bellum, rights during a war. These regulations are formal obligations, which give frame to the lawful war and show direction to the opposite parties. Grotius says that there are regulations strictly from the law of nature. A great example is that every instrument can be applicable if it is necessary to reach the major aim of war. It is obvious that today this sentence is intolerable, because technical revolution created such weapons that have power to destroy a whole country suddenly. That is why certain prohibited weapons and methods of warfare exist in international treaties. Grotius deals with the problem of traitors, who support the enemy. There is a slight distinction between the nature of dispatched goods. If these goods can be used for fighting, i.e. weapons, traders are enemies too. If these goods are luxury ones, no traitors can be found. The third situation is more problematic, because if these goods can be used in and outside a war too, the exact situation has to examine to judge the intention of the party.Groitus has interesting thoughts about prisoners. All prisoners and their descendants become slaves. It means the enemy can do anything against prisoners. By now we have certain rules how to treat with prisoners and it is a general regulation that torture and murder against prisoners is strictly prohibited.An interesting question is in connection with the law of contracts. Hostages and pledge can be typical securities to strengthen a contract. Grotius says that killing a hostage can be lawful, but inner morals order that killing is lawful only if hostage is culpable too.Grotius deals with the question of ministers, arranging debates. Looking through this huge work of Grotius we can say statement that he is the father of international law is not without basic and well structured reasons. Before the birth of his book, there were only rules and commentaries for national laws. Grotius extended them to a larger perspective, up to an international level.